Performance Of Image Cytology Features Versus Fourier Transform Infrared Spectroscopy (Ftir) Features As Diagnosis Input For Cervical Cancer Screening Tools Using Artificial Neural Network. - Mat Isa, Nor Ashidi; Yusoff, Intan Aidha; Jusman, Yessi; Sulaiman, Siti Noraini; Othman, Nor Hayati (2010)
Statistically, 471,000 new cases of cervical cancer are reported in Malaysia each year, and more than 270,000 deaths were recorded.